Avaliação pós ocupação de habitações em steel frame - Miró, Maria Fernanda Rorato Bregenski (2017)
Knowing the importance of the perception of the users of houses built with the Light Steel Frame Construction System for the improvement of the same in Brazil, this work has, through the methodology of Post-occupation Evaluation, to evaluate the acceptance and perception of the LSF constructive system by part of the user, comparing with their experiences in buildings that use traditional technologies, which are already culturally accepted; to evaluate the state of conservation of the houses and possible pathologies that arose during the occupation; besides comparing the perception of the user regarding the thermal-acoustic performance with measurements in loco. The methodology involved visits to the environment and also interviews with users through questionnaires as data collection. Through an analysis, both houses obtained satisfactory results on the part of the users, which satisfies another objective of the work, which is the development of a greater cultural acceptance for the proposed system.